Vesicular arbuscular mycorrhizal, oil palm, colonization - Nabilah Nabilah Siregar (Institut Pendidikan Tapanuli Selatan, 2017)
The role of mycorrhiza in maintaining biodiversity and ecosystems known mycorrhiza maintain the diversity of plants and increase productivity. The first thing that must be known to study the potential of vesicular arbuscular mycorrhizal is to know the diversity of these organisms. The aim of this research was to know the density of spore, colonization percentage, and types of vesicular arbuscular mycorrhizal of oil palm tree in PTPN III Batang Toru Estate. Percentage of vesicular arbuscular mycorrhizal colonization in Afdeling I by 42% and Afdeling II 34,2%. Vesicular arbuscular mycorrhizal spores knowed that there consisted of one genera Glomus.